Learning Management Systems: The Game Changer for Traditional Teaching and Learning at Adult and Higher Education Institutions (Global Journal of Human-Social Science, 2019)
This qualitative case study explored how learning management systems influence adult learners method of acquiring higher education how learning management systems influence adult learners transformative learning and how learning management systems is a game-changer for traditional teaching and learning at adult and higher education institutions This empirical study focused on the perspectives of faculty members students and academic leadership concerning learning management systems utilization benefits preference and satisfaction that influenced traditional teaching and learning at adult and higher education institutions The qualitative and quantitative research methods conducted by the scholars in this empirical study shows positive and optimistic responses from faculty members and students regarding learning management system preference utilization appreciation and satisfaction for online teachinglearning at adult and Higher education institutions The study shows the trend and directions adult and higher education institutions are taking to meet the demands and competition to deliver online education to adult learners
Keywords: learning management system; online learning; distance education; adult education